How Does Replacement Of The Axial Histidine Ligand In Cytochrome C Peroxidase By Nδ-methyl Histidine Affect Its Properties And Functions? A Computational Study - Calvin W. Z. Lee; Anthony P. Green; Sam P. de Visser; Muhammad Qadri Effendy Mubarak (Multidisciplinary Digital Publishing Institute, 2024)
Int. J. Mol. Sci. 2020, 21(19), 7133